Microstructure, Characterization and Mechanical Properties of Coal and Coal-Like Materials - Liu, Xuesheng; Tan, Yunliang; Wu, Yunhao; Li, Xuebin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In view of the general trend that the development of the global energy industry is oriented toward green, low-carbon, and efficient utilization, scientific research teams in various fields dominated by the coal industry have conducted much research on coal and coal-like materials by borrowing the technologies and concepts of modern materials science and rock mass mechanics, hoping to explore new directions for the high value-added utilization of structural coal resources and the development of new coal-like materials. On behalf of Materials, we invited you to contribute an original research article to a Special Issue on the microstructure, characterization, and mechanical properties of coal and coal-like materials. This Special Issue aimed to showcase the latest scientific and technological achievements and cutting-edge test technologies in the study of coal and coal-like materials, with exploration of their structural change characteristics and mechanical properties under various influencing factors. Hot topics to be covered include: Analysis of mechanical properties of coal and coal-like materials;Multiscale characterization of coal and coal-like materials;Development and utilization of coal resources with high added value;Void structure and seepage characteristics of coal and coal-like materials;Establishment of constitutive relationships.